(untitled) (Bangladesh Journal of Child Health, 2016)
Human immune deficiency virus (HIV) infection leading to acquired immune deficiency syndrome (AIDS) has been a major cause of illness and death among children, teens and young adults worldwide. In recent years, HIV infection rates have been increasing rapidly among teens and young adults. The three main ways HIV is passed to a very young child are: intrauterine, at the time of birth and during breast feeding. Among the teens, the virus is most commonly spread through unprotected sex, sharing needles or in very rare cases by direct contact with an open wound of an infected person or through blood transfusion. A baby born with HIV infection most likely will appear healthy. But within 2 to 3 months after birth, an infected baby might begin to appear sick, with poor weight gain, repeated infections, and enlargement of lymph nodes, liver or spleen and neurological problems. Every pregnant woman should be tested for HIV to have a better chance of preventing transmission to her unborn child. Older kids, teens and adults are tested for HIV infection and if found positive should undergo protocolized treatment. There is no vaccine to prevent HIV and AIDS although researchers are working to develop one. Thus, prevention of HIV remains of worldwide importance. Bangladesh J Child Health 2015; VOL 39 (1) :30-37